2011
DOI: 10.4319/lo.2011.56.3.1035
|View full text |Cite
|
Sign up to set email alerts
|

Spatial, seasonal, and ontogenetic variations in the significance of detrital pathways and terrestrial carbon for a benthic shark, Chiloscyllium plagiosum (Hemiscylliidae), in a tropical estuary

Abstract: Using a combination of stable isotope analyses (SIA), fatty acid profiling (FAP), and FA-specific SIA, we investigated the relative importance of terrestrial-and marine-derived carbon, and spatial (inshore vs. offshore), seasonal (wet vs. dry season), and ontogenetic variations, in the relative contribution of detrital pathways to the white-spotted bamboo shark, Chiloscyllium plagiosum in the Pearl River estuary. SIA and FAP suggested the sharks acquired carbon from both marine-and terrestrial-derived detritus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 68 publications
0
41
0
Order By: Relevance
“…Mar Ecol Prog Ser 455: [245][246][247][248][249][250][251][252][253][254][255][256] 2012 man et , Torres-Rojas et al 2010, to molecular tools including stable isotope and lipid biomarker analysis (MacNeil et al 2005, Pethybridge et al 2010, Wai et al 2011. Although stomach content analysis can provide evidence for specific dietary items, biochemical approaches have the advantage of providing information on assimilated organic substrates and can be especially helpful in complex ecosystems with multiple organic carbon substrates (Dalsgaard et al 2003, Iverson et al 2004, Whiles et al 2010.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Mar Ecol Prog Ser 455: [245][246][247][248][249][250][251][252][253][254][255][256] 2012 man et , Torres-Rojas et al 2010, to molecular tools including stable isotope and lipid biomarker analysis (MacNeil et al 2005, Pethybridge et al 2010, Wai et al 2011. Although stomach content analysis can provide evidence for specific dietary items, biochemical approaches have the advantage of providing information on assimilated organic substrates and can be especially helpful in complex ecosystems with multiple organic carbon substrates (Dalsgaard et al 2003, Iverson et al 2004, Whiles et al 2010.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…There, local primary production is often less than community respiration (Pace et al 2004, del Giorgio andPace 2008), and subsidies of allochthonous organic matter from terrestrial sources often supplement local autochthonous sources such as phytoplankton (Hoffman et al 2007(Hoffman et al , 2008, Van den Meersche et al 2009, Babler et al 2011. In contrast to temperate regions, however, the origins of the organic matter sustaining food webs and secondary production in most tropical estuaries are largely unknown (Blaber 2000, Barros et al 2010, Wai et al 2011a.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of terrestrial carbon to higher trophic levels has recently been demonstrated for the white-spotted bamboo shark Chiloscyllium plagiosum (Hemiscylliidae), a common benthic predator in the PRE, and allochthonous energy was particularly important for juvenile C. plagiosum within the inner estuary nursery grounds (Wai et al 2011a). The spadenose shark, Scoliodon laticaudus (Carcharhinidae), is sympatric with bamboo sharks in the PRE, and occurs widely in the coastal waters of the Indo-West Pacific (White and Sommerville 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even with the use of stable isotopes, there is still some controversy related to the importance of allochthony, with some studies suggesting that terrestrial detritus is important for estuarine food webs (e.g., Abrantes and Sheaves 2010, Wai et al 2011), while most did not find evidence of incorporation of terrestrial detritus by aquatic consumers (e.g., Deegan andGarritt 1997, Chanton andLewis 2002) and suggest that transported material is not available to be assimilated by aquatic consumers as it is mostly refractory (Wiegner et al 2009). …”
Section: Introductionmentioning
confidence: 99%